Tutorial Action and the Development of the Competences of the Democratic and Intercultural Citizen Exercise - Gallarday-Morales, Santiago (2019)
This article addresses tutorial and citizen development in high school students, the objective was to establish the relationship between the tutorial action and the development of democratic and intercultural citizenship exercise competencies in fifth grade students of the secondary level of public institutions of Network No. 06 of Callao. The research was quantitative, not experimental, descriptive correlational, basic and cross-sectional. The population was composed of 489 students, the sample being determined by 215 students, who were applied a questionnaire as a survey to collect information. The results show that there is a moderate and positive relationship between the tutorial action and the development of the competencies of the democratic and intercultural citizenship exercise, given that the Spearman's Rho is 0.404, with a significance value of p = .003 compared to the α = .05 where it is found that (p <α).